Compression with active movements in osteoarthritis of knee: a case study - Khatri, Subhash M.; Harsulkar, Sunil G. (International Journal Of Community Medicine And Public Health, 2017)
The objective of this case study was to find out the immediate effectiveness of an innovative approach in form of CAM (Compression with Active movements) in a woman with chronic osteoarthritis of knee. Participant was an individual with chronic osteoarthritis of knee participated in this study. The intervention was hands on manual therapy approach called compression with active movements where hamstrings muscle were compressed with therapist hands as if they were splinted or supporting by hand and simultaneously patient was asked to perform the active knee flexion and extension for three bouts of 10 repetitions. Main outcome measured in this case was pain relief in terms of visual analogue scale and active knee flexion. Pain was reduced by 3.1 cm on VAS scale and active knee flexion improved by 16 degree. Compression with active movements may be used for immediate relief of pain in chronic osteoarthritis of knee when it is associated with hamstrings spasm so as to get confidence of patient in performing active movements.